2014
DOI: 10.1186/s12913-014-0541-1
|View full text |Cite
|
Sign up to set email alerts
|

Distance decay and persistent health care disparities in South Africa

Abstract: BackgroundAccess to health care is a particular concern given the important role of poor access in perpetuating poverty and inequality. South Africa’s apartheid history leaves large racial disparities in access despite post-apartheid health policy to increase the number of health facilities, even in remote rural areas. However, even when health services are provided free of charge, monetary and time costs of travel to a local clinic may pose a significant barrier for vulnerable segments of the population, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
93
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 27 publications
5
93
0
Order By: Relevance
“…14,47 A significant component of OOP payments for people residing in rural areas and remote settings is the cost of travel to access health services. Clearly, OOP payments increases with increasing remoteness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,47 A significant component of OOP payments for people residing in rural areas and remote settings is the cost of travel to access health services. Clearly, OOP payments increases with increasing remoteness.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that even when user fees have been abolished, individuals and households still incur costs when they visit health facilities. 9,14,15 When patients turn up at a health facility to seek treatment, they often face uncertain OOP charges. In such a system, the implications for health service utilisation and health expenditure associated with visits to a health provider remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Such access to healthcare may be limited for older women in light of their multi-tasking roles and perhaps, cultural restrictions. Lack of income and limited transportation to hospitals within the continent are additional barriers which may be faced by elderly people with NCDs in their quest for proper healthcare [18, 19]. We hypothesize that these challenges may prompt older women in a South African peri-urban/township area to seek readily accessible treatment options to take care of their health conditions.…”
Section: Introductionmentioning
confidence: 99%
“…1). The geographical barrier to utilisation, manifested as a distance decay, is a well-known phenomenon in studies of healthcare utilization [37, 38, 49] and occurs when usage of health facilities declines with increasing distance [50, 51]. This feature motivates the use of probit models to characterise treatment-seeking behaviour (section 2.4).…”
Section: Methodsmentioning
confidence: 99%